Metacognitive Awareness of Classs XI Students in relation to their Self-Regulation - Kaur, Amandeep; Kaur, Navdeep (JOURNAL OF INDIAN EDUCATION, 2021)
Self-regulation is a highly adaptive attribute of human beings, and it helps the learners to plan and organise the task, set goals, and self-evaluate themselves at each step of task completion. Self-regulation has a strong association with different learning situations that are metacognitively guided. The current study examined the metacognitive awareness of Class XI students in relation to their self-regulation. The participants (n=240) were the students of five senior secondary schools of district Amritsar, Punjab. Metacognitive awareness inventory and self-regulated learning scale were used to assess the metacognitive skills and level of self-regulation among students. The relationship between metacognitive awareness was examined by using correlational and regression analysis. The difference between metacognition and self-regulation based on gender was examined by using a t-test for independent samples. The findings of the study indicated a significant and positive relationship between self-regulation and the metacognitive awareness of students. Focusing on gender, no significant differences were found in the metacognition and self-regulation of males and female students. The results of the present study are discussed in light of previous studies.